Two‐sided influence of dupilumab on alopecia areata co‐existing with severe atopic dermatitis: A case series and literature review - Masahiro Fukuyama; Misaki Kinoshita‐Ise; Yoshiko Mizukawa; Manabu Ohyama (Frontiers Media S.A., 2023)
Abstract Objectives Alopecia areata (AA) often coexists with atopic dermatitis (AD). Recently, several reports suggested that dupilumab, an interleukin 4 receptor α‐antagonist, administration could be a promising medication not only for severe AD but also for AA concomitant with AD (AD‐AA). At the same time, dupilumab has also been reported to exacerbate AA in AD‐AA cases. Thus, the efficacy of dupilumab on AA in AD‐AA cases remains controversial. Methods In this study, we retrospectively analyzed four AD‐AA cases treated with dupilumab to evaluate its influence on AD and AA. Results All cases had suffered from severe AD since childhood and their average eczema area and severity index (EASI) scores prior to dupilumab administration was 43.2 ± 15.0. Three of four cases had moderate to severe multifocal AA, which successfully recovered in response to dupilumab, accompanied by the decrease in serum thymus and activation‐regulated chemokine (TARC) levels and significant improvement of AD, achieving approximately 90% improvement of EASI scores within 3 months. In contrast, the remaining one case developed rapidly progressive hair loss 8 months after the initiation of dupilumab. In this case, AD was incompletely controlled by dupilumab with the elevation of serum TARC level despite AD improvement. The literature review found 39 dupilumab‐treated AD‐AA cases with elaborate description of clinical course; 24 cases with AA improvement, 15 cases with AA exacerbation, or new onset. Conclusions These findings alert physicians that use of dupilumab in expectation of AA improvement in AD‐AA cases can lead to unfortunate consequence in some patients.